Comparative study of electrical test methods on detecting transformer faults - Sharin Ab Ghani; Mohd Shahril Ahmad Khiar; Imran Sutan Chairul; Nor Hidayah Rahim; Mohd Hisamuddin Kamaruzaini (Institute of Advanced Engineering and Science, 2022)
Condition monitoring of distribution and power transformers is of utmost importance to utilities due to cost effectiveness concerns. The common faults that occur in transformers are short circuits and winding deformation. To date, there are many established test methods used to detect these faults. In this study, three test methods (insulation resistance (IR), transformer turn ratio (TTR), and frequency response analysis (FRA)) were compared to assess their effectiveness in detecting short circuit and winding deformation in a three-phase transformer. Based on the results, the three test methods were found to be capable of detecting short circuits. However, only TTR and FRA can detect winding deformation, and FRA can further indicate which phase is faulty. Therefore, it is concluded that FRA is more effective in detecting short circuit and winding deformation of a three-phase transformer.